If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3r = r + -1(r + 1) Reorder the terms: 7 + -3r = r + -1(1 + r) 7 + -3r = r + (1 * -1 + r * -1) 7 + -3r = r + (-1 + -1r) Reorder the terms: 7 + -3r = -1 + r + -1r Combine like terms: r + -1r = 0 7 + -3r = -1 + 0 7 + -3r = -1 Solving 7 + -3r = -1 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3r = -1 + -7 Combine like terms: 7 + -7 = 0 0 + -3r = -1 + -7 -3r = -1 + -7 Combine like terms: -1 + -7 = -8 -3r = -8 Divide each side by '-3'. r = 2.666666667 Simplifying r = 2.666666667
| -2(3x-7)=36 | | 16+4x+3=-2x-(-6x)+12-(-7) | | 5x-100=-2x+40 | | 7x-4=-11x+6 | | 25x/45=-67 | | 1+7x=-5x-23 | | -4(1+k)=-3-3k | | (3y^2-8y+1)-(2y^2-8y+8)= | | -37-x=35-9x | | -3r-12=4-r | | x-7/6=2 | | X*4=100 | | 10n+5-8n-3=12 | | 2(m+3)= | | 9-5/8x=10 | | 12-15x(-5)= | | x^2+22x=-84+10x | | 7n+29=8 | | -12x^3+9x^2=0 | | -26+4= | | -4=a-10u | | 8+x=-(x+8) | | -5-10x^2=-68 | | G=3j+4 | | y=7(-8)-26 | | -5+48= | | 16-3n=1-8n | | y=-5(-8)-35 | | (2z-7)(6+z)=0 | | y=3(-8)-72 | | 0.6t=0.9+0.4t | | 3(4z-7)=21+12z |